Elektroerozivní obrábění - Novotný, Jan; Jan Novotný (České vysoké učení technické v Praze, 2021)
Tato práce se zabývá problematikou elektroerozivního obrábění. Práce je koncipována do dvou větších celků. V první části je podrobně popsán princip dané technologie počínaje historií vzniku až po nejnovější trendy. V druhé části jsou vybrány tři nejpoužívanější typy elektroerozivního obrábění a jsou porovnány s příslušnými konkurenty. Součástí závěru práce jsou porovnávací tabulky pro usnadnění volby vhodné technologie.

This thesis is aimed at describing electric discharge machining method. Thesis is divided into two major parts. First part describes the principles of electric discharge machining and its history and current trends. In the second part, three most used types of electric discharge machining are chosen and further described with an in-depth comparison between the given types. The thesis conclusion includes comparison tables between the given types which are designed to provide all needed information regarding choice between the given types of electric discharge machining method.
Electric Discharge Machining
Keywords: Elektroerozivní obrábění; EDM; nekonvenční technologie obrábění; elektroerozivní drátové řezání; elektroerozivní hloubení; elektroerozivní vrtání; Electric Discharge Machining; EDM; Non-Convencial machining; wire electrodischarge machining; sinking electrical discharge machining; electrodischarge drilling